Governing the new NHS : issues and tensions in health service policy, governance, and management - Storey, John , 1947-; Bullivant, John; Corbett-Nolan, Andrew (Abingdon, Oxon : Routledge, 2011)
Sweeping changes have made NHS governance a crucial and contested issue. This text describes and assesses the NHS governance arrangements and accountabilities. It examines how they are working in practice, reporting on how practitioners are responding to the difficulties and paradoxes that arise
1. The architecture of NHS governance: issues and tensions -- 2. The role of regulators in the governance process -- 3. The governance of networks -- 4. Governing the commissioning organizations -- 5. Governing the provider organizations -- 6. Governance between organizations -- 7. Board development for better governance -- 8. Conclusions and the way ahead
Includes bibliographical references (p. [176]-182) and index
Keywords: National health services -- Great Britain -- Administration; Clinical Governance -- standards -- Great Britain; Clinical Governance -- organization & administration -- Great Britain; Health policy -- Great Britain; State Medicine -- Great Britain